Comparison of clinical characteristics between meth/amphetamine and synthetic cathinone users presented to the emergency department. (3rd August 2022) - Weng, Te-I; Chen, Hsien-Yi; Chin, Lengsu W.; Chou, Hsin-Hui; Wu, Meng-Huan; Chen, Guan-yuan; Chen, Ju-Yu; Shih, Chia-Pang; Lin, Chih-Chuan; Fang, Cheng-Chung
Abstract: Background: Synthetic cathinones (SC) are popular new psychoactive substances that produce sympathomimetic toxicity. Meth/amphetamine and SC have similar chemical structures and pharmacological effects. We aimed to compare the clinical characteristics between meth/amphetamine and SC users presenting to the emergency department (ED). Methods: This retrospective observational cohort study included patients who presented to six EDs from May 2017 to April 2021 with symptoms that related to recreational drug use and whose urine toxicology tests were positive only for meth/amphetamine or SC through liquid chromatography-tandem mass spectrometry. Results: There were 379 patients who tested positive only for meth/amphetamine (MA group), and 87 patients tested positive only for SC (SC groups). Patients in the MA group were older than those in the SC group (median (IQR); MA: 37.0 (30–43.7), SC: 25.0 (21.0–32.7), p < 0.001). There were no significant between-group differences in the sex distribution and initial chief complaints. Compared with the MA group, the SC group had more cases of tachycardia (≥ 135/min; MA: 29 (8.2%), SC:16 (19.0%), p = 0.0031) and hyperthermia (≥ 38 °C; MA: 31 (8.2%), SC:18 (20.7%), p = 0.001). Besides, the SC group had significantly higher levels of creatinine kinase (CK, IU/L; MA: 263 (115–601), SC: 497 (206–9216), p = 0.008) as well as a higher risk of rhabdomyolysis (CK > 1000; MA:32 (8.4%), SC: 16 (18.4%), p = 0.006) and severe rhabdomyolysis (CK > 10, 000; MA:10 (2.6%), SC:10 (11.5%), p = 001). Multivariable logistic regression analyses indicated SC group in comparison with the MA group (adjusted odds ratio: 2.732, 95% confidence interval: 1. 250–5.972, p = 0.012) was an association with the risk of rhabdomyolysis. Conclusion: Our findings demonstrate that tachycardia, hyperthermia, and rhabdomyolysis were more common among cathinone users than among meth/amphetamine users presented to EDs.